Pola Antipsikotik pada Pasien Rawat Jalan Skizofrenia di Rumah Sakit Jiwa Provinsi Lampung - Isnenia Isnenia (Jurnal Ilmiah Medicamento, 2022)
Schizophrenia as a chronic mental disorder, has increased in number in the last three decades DALYs (Disability Adjusted Life Years). Antipsychotics have been the mainstay of treatment. The use of combinations of typical/atipycal antipsychotic active substances is very often done. The purpose of this study was to look at patient characteristics and clinical characteristics including the number and type of antipsychotic combinations. This research is descriptive research with a quantitative and cross-sectional approach. Data age, gender, duration of illness, financing status, number of drugs, and the name of the antipsychotic used were taken from medical records and prescription sheets from 207 outpatients diagnosed with schizophrenia. The data was then processed and analyzed using univariate analysis. Outpatient schizophrenia patients were dominated by 62.8% male, aged 26-35 years 32.4%, duration of illness more than 12 months was 92.3%, 82.8% used health insurance, the average number of drugs prescribed was 3.5 drugs. The combination with two antipsychotics was 58%. The atypical-typical combinations (30.9%) were higher with the most risperidone-clozapine. Typical-typical combinations (19.3%) included chlorpromazine-haloperidol, trifluoperazine-chlorpromazine. Atypical-atypical combinations include risperidone-clozapine. The combination of three antipsychotics reached 7.7%. The conclusion of this study shows that the combination of antipsychotics is widely used in the treatment of schizophrenia, with two types of antipsychotics being the most widely used. The combination of risperidone-chlorpromazine was the most common at 21.7%.